Implementation Of Teacher Presence System Using Mobile-Based Geofencing & Haversine Formula Methods - Muhammad Dawamul Mughni; Putri Aisyiyah Rakhma Devi (Universitas Nahdlatul Ulama Surabaya, 2023)
Implementation of a teacher presence system using geofencing and the Haversine Formula mobile-based method provides a modern solution for accurately monitoring teacher attendance. This system utilizes geofencing technology to set virtual boundaries around certain locations and the Haversine formula to calculate the distance between the teacher's current location and the school's location. If the teacher's location is within the boundaries of the area, the system assumes the teacher is present, and if outside, the system considers the teacher absent. Attendance status is regularly updated and stored in the database, providing an efficient method for administrators to monitor teacher attendance and increase accountability. The use of this system reduces the possibility of manual errors, making it a valuable tool in education. Two tests were carried out, namely testing the accuracy of the system and testing black box testing. Accuracy testing was carried out under three conditions, namely inside the presence area, at the border of the presence area, and outside the presence area. The test was carried out 30 times and resulted in 100% accuracy. then blackbox testing also concludes that the application works in accordance with the testing that has been done. The conclusion from this research is that the higher the device and network used, the more accurate it will be.